1997
DOI: 10.1002/maco.19970480203
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption studies of water on copper, nickel, and iron using the quartz‐crystal microbalance technique: Assessment of BET and FHH models of adsorption

Abstract: In the atmospheric corrosion of copper, nickel, and iron, the adsorption of water affects the corrosion rates. Knowledge of waler adsorption and metal oxyhydroxide formation is important in understanding the atmospheric corrosion process. The purposes of the present research were (1) to measure the adsorption of water on metal surfaces as a function of temperature and relative humidity (RH) and (2) to assess Brunauer-Emmett-Teller (BET) model and Frenkel-Halsey-Hill (FHH) model for water adsorption. ln the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Lee et al 85 reported that a certain number of layers sufficient to start corrosion processes will be formed on metal surface at a critical humidity of about 60% to 70% at room temperature, depending on the substrate polarity and its surface energy. Moreover, hygroscopic contaminants such as chlorides apparently lower the critical humidity of adsorption.…”
Section: Electrolyte Layer Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al 85 reported that a certain number of layers sufficient to start corrosion processes will be formed on metal surface at a critical humidity of about 60% to 70% at room temperature, depending on the substrate polarity and its surface energy. Moreover, hygroscopic contaminants such as chlorides apparently lower the critical humidity of adsorption.…”
Section: Electrolyte Layer Formationmentioning
confidence: 99%
“…Takemoto et al 76 reported that in pure water pure Pb showed the highest susceptibility of ECM, thereby the addition of Pb increased the susceptibility, and Sn had the lowest susceptibility compared to that of Pb and Sn-40Pb solder alloy. Lee et al 82 investigated the ECM characteristic of Sn-Pb solder alloys with varying DC bias voltages under 85 C and 85% RH condition. They found that Pb was more susceptible to ECM failure than Sn in the eutectic Sn-Pb solder alloys.…”
mentioning
confidence: 99%
“…Based on existing literature, 60% RH is equivalent to ∼8 layers of atomic water on flat gold surfaces. 35 At higher relative humidity, additional water molecules adsorb too far from the surface to affect surface scattering.…”
Section: Resultsmentioning
confidence: 99%